An algebra problem by durgaprasad sahu

Algebra Level 3

If a + b + c = 3 a+b+c=3 and 1 a + b + 1 b + c + 1 c + a = 10 3 \dfrac{1}{a+b}+\dfrac{1}{b+c}+\dfrac{1}{c+a}=\dfrac{10}{3} , where a a , b b and c c are reals then find the value of 1 a + 1 b + 1 c 1 a b c \dfrac{1}{a}+\dfrac{1}{b}+\dfrac{1}{c}-\dfrac{1}{abc} .

Cannot be determined 10 63 \frac {10}{63} 0 10 9 \frac {10}9 10 27 \frac {10}{27}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Vilakshan Gupta
Feb 19, 2018

1 a + b + 1 b + c + 1 c + a = 1 3 a + 1 3 b + 1 3 c = 10 3 = ( 3 b ) ( 3 c ) + ( 3 a ) ( 3 c ) + ( 3 a ) ( 3 b ) ( 3 a ) ( 3 b ) ( 3 c ) = 10 3 3 × ( 27 6 ( a + b + c ) + a b + b c + c a ) = 10 × ( 3 a ) ( 3 b ) ( 3 c ) 81 18 ( a + b + c ) + 3 ( a b + b c + c a ) = 270 90 ( a + b + c ) + 30 ( a b + b c + c a ) 10 a b c 189 72 ( a + b + c ) + 27 ( a b + b c + c a ) = 10 a b c 21 8 ( a + b + c 3 ) + 3 ( a b + b c + c a ) = 10 9 a b c = 21 24 + 3 ( a b + b c + c a ) = 10 9 a b c a b + b c + c a 1 a b c = 10 27 \begin{aligned} \frac{1}{a+b} + \frac{1}{b+c} + \frac{1}{c+a} \\ & = \frac{1}{3-a}+\frac{1}{3-b}+\frac{1}{3-c} = \frac{10}{3} \\ & = \frac{(3-b)(3-c)+(3-a)(3-c)+(3-a)(3-b)}{(3-a)(3-b)(3-c)}=\frac{10}{3} \\ & \implies 3\times \left(27-6(a+b+c)+ab+bc+ca\right)=10 \times (3-a)(3-b)(3-c) \\ & \implies 81-18(a+b+c)+3(ab+bc+ca)=270-90(a+b+c)+30(ab+bc+ca)-10abc \\ & \implies 189-72(a+b+c)+27(ab+bc+ca)=10abc \\ & \implies 21-8(\color{#D61F06}{\underbrace{a+b+c}_3})\color{#333333}+3(ab+bc+ca)=\frac{10}{9}abc \\ & = 21-24+3(ab+bc+ca) = \frac{10}{9}abc \\ & \implies \frac{ab+bc+ca-1}{abc} = \frac{10}{27} \end{aligned}

Also, 1 a + 1 b + 1 c 1 a b c = a b + b c + c a 1 a b c = 10 27 \frac{1}{a}+\frac{1}{b}+\frac{1}{c}-\frac{1}{abc}=\frac{ab+bc+ca-1}{abc}=\boxed{\dfrac{10}{27}}

Chew-Seong Cheong
Feb 20, 2018

1 a + b + 1 b + c + 1 c + a = 10 3 Since a + b + c = 3 1 3 c + 1 3 a + 1 3 b = 10 3 ( 3 a ) ( 3 b ) + ( 3 b ) ( 3 c ) + ( 3 c ) ( 3 a ) ( 3 a ) ( 3 b ) ( 3 c ) = 10 3 27 6 ( a + b + c ) + a b + b c + c a 27 9 ( a + b + c ) + 3 ( a b + b c + c a ) a b c = 10 3 Again a + b + c = 3 9 + a b + b c + c a 3 ( a b + b c + c a ) a b c = 10 3 27 + 3 ( a b + b c + c a ) = 30 ( a b + b c + c a ) 10 a b c 27 ( a b + b c + c a ) 27 = 10 a b c Divide both sides by 27 a b c 1 a + 1 b + 1 c 1 a b c = 10 27 \begin{aligned} \frac 1{a+b} + \frac 1{b+c} + \frac 1{c+a} & = \frac {10}3 & \small \color{#3D99F6} \text{Since }a+b+c = 3 \\ \frac 1{3-c} + \frac 1{3-a} + \frac 1{3-b} & = \frac {10}3 \\ \frac {(3-a)(3-b)+(3-b)(3-c)+(3-c)(3-a)}{(3-a)(3-b)(3-c)} & = \frac {10}3 \\ \frac {27-6{\color{#3D99F6}(a+b+c)}+ab+bc+ca}{27-9{\color{#3D99F6}(a+b+c)}+3(ab+bc+ca)-abc} & = \frac {10}3 & \small \color{#3D99F6} \text{Again }a+b+c = 3 \\ \frac {9+ab+bc+ca}{3(ab+bc+ca)-abc} & = \frac {10}3 \\ 27 + 3(ab+bc+ca) & = 30(ab+bc+ca)-10abc \\ 27(ab+bc+ca) - 27 & = 10abc & \small \color{#3D99F6} \text{Divide both sides by }27abc \\ \frac 1a+\frac 1b + \frac 1c - \frac 1{abc} & = \boxed{\dfrac {10}{27}} \end{aligned}

Nice.. By the way from where you are sir..

durgaprasad sahu - 3 years, 3 months ago

Log in to reply

Look at my profile. I am from Malaysia.

Chew-Seong Cheong - 3 years, 3 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...